Implementation and evaluation of an analytical method for a novel derivatizing agent to measure 4, 4'-methylene diphenyl diisocyanate atmospheres. Issue 8 (2nd August 2016) - Puscasu, Silvia; Aubin, Simon; Spence, Mark; Gagné, Sébastien
ABSTRACT: Accurate measurement of 4, 4'-methylene diphenyl diisocyanate (MDI) atmospheres is a challenge since the molecule is both chemically reactive and likely to be present in aerosol form when heated and sprayed because of its low vapor pressure. Meeting this challenge requires optimizing both the sampling device used and the derivatization agent employed to stabilize the isocyanate functional group. This study describes the use of a novel derivatization reagent for isocyanate sampling to address the challenge of MDI aerosol exposure sampling. Like most conventional derivatizing agents for isocyanates, 1, 8-diaminonapthalene (DAN) reacts with isocyanate functional groups to form a urea. However, unlike other isocyanate derivatizing agents, the sample workup procedure with DAN includes a second step which yields a single analyte molecule, perimidone, for each isocyanate group. This feature gives DAN the unique ability to assess exposure to "total reactive isocyanate group" (TRIG). The analytical method implemented to quantitate the perimidone uses liquid chromatography coupled with tandem mass spectrometry. Positive mode ionization led to LOD and LOQ of 10 ng/mL and 34 ng/mL, respectively. The dynamic range was from 50–2000 ng/mL (with R 2  ≥ 0.990), which corresponds to TRIG concentrations in air from 0.07–3.04 µg/m 3, assuming 60 min of sampling at 10 L/min (based on use of the CIP-10M sampler). The intra-day and inter-day analytical precisions were <4% for all of the concentration levels tested, and the accuracy was within an appropriate range of 98 ± 2%. Minimal matrix effect was observed, and a total recovery of 109% was obtained. The approach seems to be promising for TRIG measurements and further work is planned to establish DAN method behavior in samplers used for workplace monitoring.